2D reflectometry for the investigation of polymer interfaces: off-specular neutron scattering. (13th July 2021) - Hafner, Aljoša; Gutfreund, Philipp; Toperverg, Boris P; Geoghegan, Mark; Sferrazza, Michele
Abstract: Specular and off-specular neutron reflectometry have been used in a combined approach to study thin polymer films. Our goal in this work is to illustrate the power of the off-specular scattering technique to probe the properties of the buried interface of immiscible polymer bilayers of deuterated polystyrene and protonated poly(methyl methacrylate) (h-PMMA). The diffuse scattering stemming from these systems is discussed in relation to thermal fluctuations at the polymer/polymer interface, providing a means to extract in-plane correlation lengths from buried interfaces. In addition the onset of hole formation in the top layer is evidenced by the diffuse scattering, not easily detectable by specular reflection alone.